Labour Regulations, Contractualization and Industrial Performance: Three-dimensional Panel Evidences from Indian Manufacturing Sector. (March 2015) - Sofi, Irfan Ahmad; Sharma, Pritee
This study analyzes the impact of spiralling growth in usage of contractual labour, in the context of stringent pro-worker labour regulations, on industrial labour productivity and employment generation. We obtain a quantitative measure of 'stringency of labour regulations' by applying majority rule on three different measures used in the literature. The results show that average labour productivity increases with the increase in the ratio of permanent workers to contractual workers, unless the industries are not operating in states having rigid/pro-worker labour regulations—which implies a negative impact of contractualization on labour productivity. Besides, the results show that the rigid/pro-worker labour regulations have negative impact on employment generation; it is especially discernible in labour-intensive industries.